2019
DOI: 10.3846/mma.2019.021
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Analysis to Explain the Numerical Anomalies in the Family of Ermakov-Kalitlin Type Methods

Abstract: In this paper, we study the dynamics of an iterative method based on the Ermakov-Kalitkin class of iterative schemes for solving nonlinear equations. As it was proven in ”A new family of iterative methods widening areas of convergence, Appl. Math. Comput.”, this family has the property of getting good estimations of the solution when Newton’s method fails. Moreover, the set of converging starting points for several non-polynomial test functions was plotted and they showed to be wider in the case of proposed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We denote scheme (10) as the Budzco x-family or PM. Cordero et al in [13] carried out an in-depth study on the dynamics of the Budzco family and determined the convergence properties that allow this method to have a stable dynamical behavior for parameter values close to 0. They called the accelerating factor of the second step,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We denote scheme (10) as the Budzco x-family or PM. Cordero et al in [13] carried out an in-depth study on the dynamics of the Budzco family and determined the convergence properties that allow this method to have a stable dynamical behavior for parameter values close to 0. They called the accelerating factor of the second step,…”
Section: Introductionmentioning
confidence: 99%
“…This uniparametric family of methods managed to improve Newton's, both in order of convergence [12] and in providing much larger basins of attraction. They showed that, for small values of the parameter, the basins of attraction that did not correspond to the roots of the polynomial were indeed small [13].…”
Section: Introductionmentioning
confidence: 99%